Conceptual metaphor as a linguomental tool of reality knowledge: identification problem - Vilchynska, Tetiana (2021)
The article investigates conceptual metaphor as a linguo-instrumental tool by which a person is able to know, evaluate and transform the world. The history of metaphor study has been considered in detail, from its complete denial to understanding as a mechanism of objective reality cognition, and it has been found that most approaches to the interpretation of metaphor were demonstrated in the twentieth century. In particular, it has been considered as a means of forming concepts, and as a semantic-two-dimensional, clearly connoted unit, and as a figurative structure of language, as a marker of idiosyncrasy, and as an object of linguistic and cultural research etc. The twentieth century witnessed the emergence of new scientific linguistic directions, which laid the foundations for understanding the conceptual metaphor associated with understanding the processes of transformation of mental categories into the language during cognition of the world, interpretation of metaphorical meaning, mechanisms of metaphorical renaming and suggestion, and manipulative potential of metaphor, etc. Within different scientific approaches a metaphor is considered as a mental phenomenon, an important way of creating concepts in the language world, which contributed to the emergence of new theories of cognitive study of metaphors as descriptive theory blends, metaphorical modelling, cognitive-onomastic analysis, etc. Further study of the conceptual metaphor, primarily on specific textual material, will reveal the cognitive-linguistic mechanisms of a person, taking into account national specifics, to identify the deep links between the language of the people and its intellectual heritage.